A novel hybrid silk-fibroin/polyurethane three-layered vascular graft: towards in situ tissue-engineered vascular accesses for haemodialysis. (31st January 2019) - van Uden, Sebastião; Vanerio, Noemi; Catto, Valentina; Bonandrini, Barbara; Tironi, Matteo; Figliuzzi, Marina; Remuzzi, Andrea; Kock, Linda; Redaelli, Alberto C L; Greco, Francesco G; Riboldi, Stefania A
Abstract: Clinically available alternatives of vascular access for long-term haemodialysis—currently limited to native arteriovenous fistulae and synthetic grafts—suffer from several drawbacks and are associated to high failure rates. Bioprosthetic grafts and tissue-engineered blood vessels are costly alternatives without clearly demonstrated increased performance. In situ tissue engineering could be the ideal approach to provide a vascular access that profits from the advantages of vascular grafts in the short-term (e.g. early cannulation) and of fistulae in the long-term (e.g. high success rates driven by biointegration). Hence, in this study a three-layered silk fibroin/polyurethane vascular graft was developed by electrospinning to be applied as long-term haemodialysis vascular access pursuing a 'hybrid' in situ engineering approach (i.e. based on a semi-degradable scaffold). This Silkothane ® graft was characterized concerning morphology, mechanics, physical properties, blood contact and vascular cell adhesion/viability. The full three-layered graft structure, influenced by the polyurethane presence, ensured mechanical properties that are a determinant factor for the success of a vascular access (e.g. vein-graft compliance matching). The Silkothane ® graft demonstrated early cannulation potential in line with self-sealing commercial synthetic arteriovenous grafts, and a degradability driven by enzymatic activity. Moreover, the fibroin-only layers and extracellular matrix- like morphology, presented by the graft, revealed to be crucial in providing a non-haemolytic character, long clotting time, and favourable adhesion of human umbilical vein endothelial cells with increasing viability after 3 and 7 d. Accordingly, the proposed approach may represent a step forward towards an in situ engineered hybrid vascular access with potentialities for vein-graft anastomosis stability, early cannulation, and biointegration.